Language Learning of Gifted Individuals: A Content Analysis Study - Beria Gokaydin; Basak Baglama; Huseyin Uzunboylu (Universidad Nacional de Colombia, 2017)
This study aims to carry out a content analysis of the studies on language learning of gifted individuals and determine the trends in this field. Articles on language learning of gifted individuals published in the Scopus database were examined based on certain criteria including type of publication, year of publication, language, research discipline, countries of research, institutions of authors, key words, and resources. Data were analyzed with the content analysis method. Results showed that the number of studies on language learning of gifted individuals has increased throughout the years. Recommendations for further research and practices are provided.